In vitro generation of cytotoxic T lymphocytes against mutated ras peptides - Juretić, Antonio (Radiology and oncology (Ljubljana), 1998)
Mutations of the ras proto-oncogenes represent frequent genetic alterations inhuman cancers. These, mutations appear as single-point mutations causing single amino acid substitutions at residues 12, 13 or 61 (activated p21 ras proteins). Therefore, peptides encompassing ras mutations appear to represent an appealing target for active immunotherapy procedures. By using a computer program, selertir appropriate HLA-A2.1 binding motifs from defined protein sequences, ras nonapeptides encompassing mutatinus in positions 12 and 61 witha putative binding capacity for HLA-A2.1 molecules were identified and synthesized. Generation of primary cytotoxic T cell lymphocyte (CTL) response was attempted by weekly restimulations of peripheral blood lymphocytes from healthy donors in the presence of irradiated autologous Epstein Barr virus transformed lymphoblastoid cells (EBV cell lines) and IL-2 arrd IL-4. Periodicaly, cultured cells were tested for their killing capacity using as target cells HLA-A2.1+ EBV cells previously pulsed with different combinationsof the peptides under investigation. After eight rounds of restimulation reproducible cytotoxic activity against EBV target cells pulsed with two nonamers encompassing ras 61 GIn Leu mutation was detectable in one donor. Thus, the results obtained indicate that it is possible to induce from PBMC of healthy donors CTL specific for peptides encompassing 61 GLN LEU ras gene mutation following repeated weekly in vitro restimulations.
Keywords: Oncogene protein p21(ras); Point mutation; T-lymphocytes, cytotoxic